Psychometric properties of the Quiet Ego Scale (iQES) within the Italian cultural context - Bernabei, Laura; Silvestrini, Cristiana; Grimaldi, Lucrezia Andrea; Piserchia, Valentina; Riggio, Francesco; Marino, Giovanni; Valente, Donatella; Pompili, Enrico (Frontiers in Psychology, 2024)
Introduction The quiet ego indicates a more compassionate conception of self-identity that integrates others into the self by lowering the intensity of the ego and enhancing the awareness of the present moment. The Quiet Ego Scale (QES) is a 14-item self-report measure of quiet ego, and it is composed of the following four psychological domains: detached awareness, inclusive identity, perspective taking, and growth. The present study aimed to test the psychometric properties of the Quiet Ego Scale within the Italian cultural context (iQES). Methods A total of 160 Italian university students aged between 20 and 42 years, with a mean age of 22.85 years (SD = 3.41), completed the measures of the iQES and of other psychological dimensions. The psychometrics properties of iQES were assessed based on its internal consistency, test-retest reliability, and construct validity through comparisons with other correlated psychological measures. Results Analyses confirmed the psychometrics properties of iQES. As in previous studies, the quiet ego was positively associated with the indicators of resilience (p < 0.01), happiness (p < 0.05), self-esteem (p < 0.01), and psychological wellbeing (p < 0.01). Discussion The study discussed the possible uses of the iQES in the field of mental health, specifically focusing on improving adherence to psychological therapies and enhancing psychological and social well-being. The results indicated strong psychometric properties of the iQES in measuring the quiet ego construct. Our findings enrich the literature on the validity of the iQES and highlight the multidimensional nature of the quiet ego construct.